ANALISIS KUALITAS MIKROBIOLOGI KEFIR SUSU KAMBING YANG DIPEROLEH DARI HOME INDUSTRI DIBERGAS KAB . SEMARANG - Alfiyaturrakhma, Untsa; Puspitaningrum, Anisa Nova; Dahliyanti, Novita Dwi (Jurnal Farmasi & Sains Indonesia, 2025)
Kefir is a fermented milk product known for its health benefits, primarily due to its probiotic microorganism content. One type of milk that is increasingly popular for making kefir is goat's milk, as it has a composition that is easier to digest and has high nutritional potential. However, the microbiological quality of goat milk kefir needs to be thoroughly analyzed to ensure its safety and probiotic effectiveness. The presence of microorganisms such as lactic acid bacteria, yeast, and potential pathogenic contaminants plays a crucial role in determining the quality of kefir, both in terms of health benefits and product stability. Therefore, analyzing the microbiological quality of goat milk kefir is essential as a foundation for developing safe, high-quality, and nutritious functional food products. Research Objective : This study aims to analyze the microbiological quality of kefir made from goat’s milk, with a focus on identifying and quantifying the dominant microorganisms involved in the fermentation process, such as lactic acid bacteria and yeast. Research Method: The analysis of microbiological quality was carried out using the Total Plate Count (TPC) method. The counts of bacteria and yeast were conducted in duplicate. The results were then compared to the Indonesian National Standard (SNI) for fermented beverages.